The influence of washed microbiota transplantation on menstruation in female patients of childbearing age - Wu, Qingting; Wang, Mingzhu; Yang, Juan; Wang, Jiangyan; Feng, Shuo; Lu, Shenghua; Qin, Zhichu; He, Xingxiang; Wu, Lei (Frontiers in Endocrinology, 2026)
Background and aimsMenstrual disorders are closely related to the disorder of gut microbiota. This study aims to explore the impact of Washed microbiota transplantation (WMT) on the quality of life, depression and anxiety scale scores, and menstrual conditions of female patients of childbearing age.MethodsThe data of female patients of childbearing age who received WMT at the First Affiliated Hospital of Guangdong Pharmaceutical University from February 2023 to February 2025 were collected. A comparative analysis was conducted on the effects of SF-36, SDS, SAS and menstrual conditions in female patients of childbearing age before and after WMT treatment. The changes of gut microbiota before and after WMT were analyzed by 16S rRNA gene sequencing.ResultsA total of 23 female patients of childbearing age were included in this study. WMT significantly improved the scores of GH, SF, MH, RE and VT in SF-36 of female patients of childbearing age and significantly reduced the scores of SDS and SAS (P < 0.05). The MDQ score was negatively correlated with the PF, BP, GH, VT, RE and MH scores in SF-36, and positively correlated with the SDS and SAS scores (P < 0.05). WMT enhanced the α diversity of gut microbiota in female patients of childbearing age, and the Chao1 and Shannon indices were statistically significant (P < 0.05). At the same time, the relative abundance of Dialister, Bifidobacterium, Faecalibacterium, Roseburia and Fusobacterium increases. The relative abundances of Bacteroides, Agathobacter, Prevotella, Escherichia-Shigella and Ruminococcus decreased.ConclusionsWMT treatment can effectively improve the quality of life score of female patients of childbearing age and reduce the scores of depression and anxiety scales. WMT can increase the diversity and abundance of gut microbiota in female patients of childbearing age and improve menstrual conditions, which provides new ideas for future clinical treatment.